PENGARUH TARIF DAN SISTEM PERPAJAKAN TERHADAP NIAT MELAKUKAN PENGGELAPAN PAJAK - Dewi Kusuma Wardani; Nurfitri Rahmawatiningsih (Jurnal Bina Akuntansi, 2023)
This study aims to examine whether tax rates and the taxation system affect the intention to commit tax evasion. This study took a sample of students at the Tamansiswa University of Yogyakarta. In this study the authors used a sampling technique using covenience sampling, in collecting data the authors used a questionnaire. From distributing the questionnaires, 100 respondents were obtained. The results of this study indicate that the tax rate has a positive effect on the intention to commit tax evasion. The tax system has no effect on the intention to commit tax evasion.